Social origins and industrial trends in the development of today’s art practices - I. K. Pokulyta; O. S. Mykhailenko (Ukrainian Cultural Studies, 2022)
The article considers the social preconditions and socio-cultural context of the formation of art practices as a cultural phenomenon of the XX century and identifies the causes and features of sectoral influence on other forms of activity in modern conditions of digitalization of social space. It is noted that the process, which reflected the binary stratification of high culture and "one-dimensional" (according to H. Marcuse) civilization, accumulated protests of the last century and formed in the structure of society field of practice – art practice, appears in modern culture in a new capacity construction of socially demanded spheres of interaction. Hypertext, interaction, co-creation, as characteristic features of the culture of postmodernism determine the principles and approaches of modern Internet, virtual, media practices. Network art practices, art projects, virtual exhibitions – what became possible with the beginning of digitalization, was a few decades ago rather an aesthetic experiment, marking the contours of creativity. The development of digital technologies, with which various spheres of activity are fused today, has formed fundamentally different conditions for the transit of practices, instant real implementation in various fields of human activity. The article provides examples of appeals to such areas of actualization of art technologies as education, psychology, social work and more. The article states that art practices, as a specific format of creativity of an experimental, interactive, dialogic nature, which absorbed various intentions of the culture of the XX century: protest moods, demarcation and at the same time borrowing of artistic traditions, acute presentation of social problems, etc., occupies a place in the development of information culture XXI century leading place in visualization of future prospects, new contours of digital civilization. However, the extent of their involvement was determined by factors of an individual, subjective nature. It is the information processes, network interactive communication, and the singularity of the fields of practice in various spheres of activity that determined the new order of introducing art practices into a wide spectrum of the sectoral development of society.